Vulnerabilidade socioambiental urbana: proposta de diagnóstico e de metodologia para a cidade de Garanhuns – PE - Costa, Samuel Othon de Souza (2023)
Urbanization transforms natural environments into artificial ones, imagining the most desired ecosystem for society, superimposing and pressuring natural elements to socioeconomic interests, set in capitalismo and generating inequalities. Thinking of the city as a space of prominence between society and nature, the issue to be discussed is about the social, economic and environmental imbalance. Associated with risks is urban socioenvironmental vulnerability, also linked to environmental and social factors and elements, however, it exposes the different conditions of fragility of social groups to risks.The problem identified in this work stems from the difficulty of establishing parameters and indicators for the elaboration of urban planning and management, taking into account the interaction between economic, social and environmental factors as a key to understanding socioenvironmental vulnerability. Therefore, the following problems were defined in the research. What indicators can be used for an urban socioeconomic vulnerability index? How do society's modifications to the physical environment contribute to the dynamics of vulnerability in the city of Garanhuns? As a hypothesis for the construction of the thesis, it is based on the idea that the integration of indicators with environmental parameters, criticality and support capacity in a GIS environment, proposing a socioenvironmental vulnerability index, define the most vulnerable urban areas. In this perspective, the city of Garanhuns faces urban and environmental problems, as it is a city in the process of growth with uneven planning and management, where the urban spaces that are less affected by socio-environmental problems will be those with the population with the highest purchasing power, while the ones with the greatest impact will be the ones with the lowest acquisition. From the contextualization of the subject studied, this work has the following objective: to propose social, economic and environmental indicators, which can be integrated into a Geographic Information System, generating the Socioenvironmental Vulnerability Index of the city of Garanhuns. In this sense, the sets of techniques and tools of geoprocessing were used, among them it can be highlighted remote sensing, photogrammetry, geographic information systems, map algebra, among others. For the elaboration of the urban socioenvironmental vulnerability index applied to the city ofGaranhuns, the methodological principles of the integration of socio-environmental indicators in the light of physical, social and temporal aspects were considered, aiming at the analysis of social vulnerability to natural and technological risks. The Analytical Hierarchy Process or "Analytic Hierarchy Process - AHP" method was also used. In the end, it was obtained that the relation to the socioenvironmental vulnerability of Garanhuns is perceived that the largest portion is destined to the Medium class with about 9.20Km², followed by Low with 7.26Km² and High with 5.25Km², indicating that Garanhuns has a fairly intermediate scenario in relation to its socio-environmental risk areas. It is interesting that with the passage of time, the always very fast urban dynamics, the city of Garanhuns may present other types of data on vulnerability, since this proximity to the intermediate can place the city in a low or high socioenvironmental risk in 10 years for example. Again, it is important to emphasize the role of public agentes in overcoming and improving the living conditions of the population, infrastructure and support capacity in the urban area. Thus, it is also interesting that the extremes of the socioenvironmental vulnerability index of the city of Garanhuns are the smallest calculated areas, Very High with 3.57Km² and Very Low with 3.70Km². However, they are not reasons for less concern, especially the first, since they are áreas with environmental and social vulnerabilities, resulting in localities with urban deficiencies and lack of access to essential public services. On the other hand, areas with Very Low socioenvironmental vulnerability should not be understood as not needing care and attention, but rather, maintenance and always promoting quality of life and sustainable development. In general, the neighborhoods with the highest index showed socio-environmental vulnerability were Dom Helder Câmara, São José, Magano and Santo Antônio, respectively. Those that presented lower risks were Severiano Morais Filho, Novo Heliópolis, Dom Thiago Posima and Heliópolis. By addressing socioenvironmental vulnerability in Garanhuns, it was possible to promote a more resilient, equitable and sustainable city, where the negative impacts of the interactions between social and environmental vulnerability are mitigated and opportunities for growth and prosperity are expanded for all its inhabitants. In addition, it is essential to invest in resilient infrastructure, early warning systems and risk management strategies to reduce exposure to natural disasters.